2008
DOI: 10.1086/524150
|View full text |Cite
|
Sign up to set email alerts
|

The Right‐to‐Left Shunt of Crocodilians Serves Digestion

Abstract: All amniotes except birds and mammals have the ability to shunt blood past the lungs, but the physiological function of this ability is poorly understood. We studied the role of the shunt in digestion in juvenile American alligators in the following ways. First, we characterized the shunt in fasting and postprandial animals and found that blood was shunted past the lungs during digestion. Second, we disabled the shunt by surgically sealing the left aortic orifice in one group of animals, and we performed a sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 34 publications
3
55
0
Order By: Relevance
“…In addition to the lack of effect of LV on growth rate, there was no influence on conversion efficiency (GCE) or the metabolic response to feeding (SDA). A number of studies on crocodilians have proposed that increased R-L shunt during digestion facilitates gastric acid secretion by supplying CO 2 -rich blood to the stomach (Farmer et al, 2008;Gardner et al, 2011;Jones, 1991), andFarmer et al (Farmer et al, 2008) showed that gastric digestion was delayed when the capacity to R-L shunt was abolished in alligators. Crotalus also exhibit considerable gastric acid secretion upon ingestion of meals (Andrade et al, 2004) and the resulting alkalinisation of the blood is similar to that of alligators (Arvedsen et al, 2005; Busk et al, 2000).…”
Section: Growth and Feeding Efficiency Is Not Affected In Snakes Unabmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the lack of effect of LV on growth rate, there was no influence on conversion efficiency (GCE) or the metabolic response to feeding (SDA). A number of studies on crocodilians have proposed that increased R-L shunt during digestion facilitates gastric acid secretion by supplying CO 2 -rich blood to the stomach (Farmer et al, 2008;Gardner et al, 2011;Jones, 1991), andFarmer et al (Farmer et al, 2008) showed that gastric digestion was delayed when the capacity to R-L shunt was abolished in alligators. Crotalus also exhibit considerable gastric acid secretion upon ingestion of meals (Andrade et al, 2004) and the resulting alkalinisation of the blood is similar to that of alligators (Arvedsen et al, 2005; Busk et al, 2000).…”
Section: Growth and Feeding Efficiency Is Not Affected In Snakes Unabmentioning
confidence: 99%
“…These hypotheses can be separated into two categories, where one group proposes that shunts are required for normal physiological function, such as providing myocardial oxygenation (Farmer, 1997) or avoidance of plasma filtration into the lungs (Burggren, 1982), while the other group argues that shunts provide important physiological advantages that improve organismal 'fitness', such as reducing cardiac energy expenditure (Burggren, 1987), regulating metabolic rate (Hicks and Wang, 1999;, providing protons for gastric acid secretion (Farmer et al, 2008;Jones and Shelton, 1993) or minimizing ventilation/perfusion (V/Q) mismatching in the lungs (West et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…However, in crocodilians, an elevated oxygen consumption associated with digestion may be an exception. A combination of unique anatomical features of the crocodilian cardiovascular system (Hicks, 1998) combined with physiological measurements fostered the idea that increased R-L shunts serve to fuel the gastric mucosa with acidic proton-rich blood during digestion in alligators (Farmer et al, 2008;Gardner et al, 2011;Jones and Shelton, 1993). Central to this proposal is the observation that the crocodilian coeliac artery appears as a continuation of the left aortic arch, which indicates that the stomach is preferentially perfused with CO 2 -rich blood from the right ventricle (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Jones, 1996;Webb, 1979). In support for elevated (systemic) arterial partial pressure of CO 2 (P CO2 ) governing acid secretion, Farmer et al (2008) reported slower digestion after surgical removal of the left aorta in alligators. However, a number of other studies show that growth is not affected by similar procedures (Eme et al, 2009(Eme et al, , 2010, and it is possible that the slower digestion stems from reduced perfusion of the gastrointestinal organs after occlusion of the left aortic arch (Hicks and Wang, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Ectotherms with their much lower metabolic demands (than endotherms) can tolerate the reduction in systemic arterial blood oxygen generated during shunting, even during exercise. Moreover, widespread shunting in extant reptiles has led to suggestions that this is a highly derived trait with certain distinct advantages (e.g., as an aid to digestion or in maintaining pressure balances; see references in Hicks, 1998;Farmer et al, 2008;e.g., as an aid to digestion or in maintaining pressure balances; see references in Hicks, 2002;Seymour et al, 2004). While many compelling arguments are made for the adaptive significance of shunting, given its phylogenetic distribution and the presence of central vascular shunts during the embryonic stages of all vertebrates, it is possible that shunting is a plesiomorphic vertebrate character lost in adult endotherms (Hicks, 2002).…”
Section: Introductionmentioning
confidence: 99%